Adverse Environmental Exposures During Gestation and Childhood: Predictors of Adolescent Drinking. (23rd August 2016) - Cornelius, Marie D.; De Genna, Natacha; Goldschmidt, Lidush; Larkby, Cynthia; Day, Nancy
ABSTRACT: Adverse conditions, including exposures to drugs and other environmental influences during early development, may affect behaviors later in life. This study examined the role of environmental influences from the gestation and childhood on adolescent drinking behavior. 917 mother/offspring dyads were followed prospectively from pregnancy to a 16-year follow-up assessment. Interim assessments occurred at delivery, 6, 10, and 14 years. Prenatal exposures to alcohol, tobacco, and marijuana were measured during gestation. Data were collected at each phase on childhood environment, including parenting practices, quality of the home environment, maternal depression and hostility, and lifetime exposure to child maltreatment and community violence. Alcohol outcomes were offspring age of drinking initiation and level of drinking at age 16 years. Cox Proportional Hazards ratios were used to model offspring age of drinking initiation. Logistic regression analyses were used to evaluate significant predictors of drinking level. Childhood environment, including less parental strictness, greater exposure to violence and childhood maltreatment, significantly predicted earlier age of alcohol initiation. Level of drinking among the adolescent offspring was significantly predicted by prenatal exposure to alcohol, less parental strictness, and exposures to maltreatment and violence during childhood. Whites and offspring with older mothers were more likely to initiate alcohol use early and drink at higher levels. Early and heavier alcohol use was associated with early exposures to adversity such as prenatal alcohol exposure, and child exposures to maltreatment and violence. These results highlight the importance of environmental adversity and less effective parenting practices on the development of adolescent drinking behavior.